Succession of founding microbiota in an anaerobic baffled bioreactor treating low-temperature raw domestic wastewater. Issue 4 (7th March 2022) - Vanzin, Gary; Pfluger, Andrew; Almstrand, Robert; Figueroa, Linda; Munakata-Marr, Junko
Abstract : Spatiotemporal development of anaerobic seed sludge in a new ABR after transfer from a long-running ABR treating low-temperature domestic wastewater. Abstract : Continuously operated pilot- and full-scale anaerobic baffled reactors (ABRs) treating low-temperature raw domestic wastewater are currently few in number but offer significant advantages. As ABRs treating domestic wastewater become more prevalent, engineers and operators face the practical challenge of effectively transferring and seeding anaerobic sludge from existing "donor" ABRs to newly constructed ABRs. Unlike activated sludge, which predominantly consists of relatively fast-growing aerobic heterotrophic bacteria, anaerobic microbiota are slower-growing and the community structure may be impacted by process disturbances during bioreactor start-up. Examining the spatiotemporal development of anaerobic microbiota after transfer can enhance understanding of start-up dynamics in engineered anaerobic bioreactor systems. To understand the impacts of sludge transfer and seeding from an existing ABR operated for 3.5 years treating raw, low-temperature domestic wastewater to a new, similarly configured ABR treating a different raw domestic wastewater stream, influent wastewater and sludge microbiota samples were withdrawn biweekly for 275 days and used to characterize changes to the microbial community structure over time in both ABRs. Results suggest that the donor ABR communities maintained relatively consistent structure over time, but the microbial communities in the receiving bioreactor experienced two apparent successional trajectories post-inoculation. The first trajectory, which lasted for ∼120 days, showed increasing divergence between communities in the two ABRs. This trajectory was marked by lower wastewater temperatures (12–14 °C, with extreme lows of 8 °C) and numerous disturbances to the sludge blankets. A second successional trajectory, observed when wastewater temperatures increased (>16 °C) and disturbances were eliminated, was marked by significant increases in the relative abundance of Euryarchaeota, especially Methanosaeta (" Methanothrix "), and increasing convergence of microbial communities in complementary donor and receiving bioreactor compartments. Further, the relative abundance of founding microbial community members significantly decreased during the first successional trajectory but significantly increased, or rebounded, during the second successional trajectory. The results of this study indicate that an anaerobic sludge inoculum can be effectively transferred from a long-running ABR treating raw, low-temperature domestic wastewater to a new ABR, and that similar performance can be achieved despite differing environmental conditions and disturbances to the sludge blanket microbial communities during start-up of the new ABR.